Regulatory significance of terminator: A systematic approach for dissecting terminator-mediated enhancement of upstream mRNA stability - Jia-Wei Ren; Jin-Peng Zhang; Zi-Lun Mei; Jia-Yi Shao; Guo-Qiang Xu; Hui Li; Jin-Song Gong; Xiao-Mei Zhang; Jin-Song Shi; Xiao-juan Zhang; Zheng-hong Xu (Synthetic and Systems Biotechnology)
The primary function of terminators is to terminate transcription in gene expression. Although some studies have suggested that terminators also contribute positively to upstream gene expression, the extent and underlying mechanism of this effect remain largely unexplored. Here, the correlation between terminating strength and upstream mRNA stability was investigated by constructing a terminator mutation library through randomizing 5 nucleotides, assisted by FlowSeq technology, terminator variants were categorized based on the downstream fluorescence intensity, followed by high-throughput sequencing. To examine the impact of terminators on mRNA stability, the abundance of downstream gene transcripts for each terminator variant was quantified through cDNA sequencing. The results revealed that the transcript abundance controlled by strong terminators was, on average 2.2 times greater than those controlled by weak terminators on average. Moreover, several distinct features could be ascribed to high relative abundance of upstream gene transcript, including a high GC content at the base region of hairpin, and a high AT content in downstream of the U-tract. Additionally, these terminators showed a free energy between −28 and −22 kcal/mol, and a stem length of 14 nt. Finally, these features ascribed the upstream beneficial terminator were validated across various expression systems. By incorporating the optimal terminator downstream of RSF, GSH and HIS in three different strains, the fermentation productions-NMN SAM and VD13 exhibited a remarkable enhancement of 30 %–70 %. The findings presented here uncovered the terminator characteristics contributed to the upstream mRNA stability, providing guiding principles for gene circuit design.